Role of calcium-phosphorus metabolism in periodontal tissue resorption in rats - Cheremisina, V. F. (Journal of Education, Health and Sport, 2017)
In the article presented the results of the study of calcium-phosphorus metabolism in rats with alveolitis. The analysis of biochemical markers of bone turnover in the blood and urine of the animals revealed significant shifts calcium-phosphorus metabolism in rats with alveolitis and soft tissues involved in periodontal resorption. The content of calcitonin is not critical in the mechanisms of resorption of the periodontal soft tissues. A negative correlation relationship between the level of the ionized calcium content in blood serum calcitonin in rats with alveolitis.